Active involvement of people with intellectual disabilities in health research – A structured literature review. (October 2015) - Frankena, Tessa Kim; Naaldenberg, Jenneken; Cardol, Mieke; Linehan, Christine; van Schrojenstein Lantman-de Valk, Henny
Highlights: Knowledge of inclusive health research is scarce. Theories and methods seem to be of little value to inclusive health research. Added value relates to improved quality and validity, but is not formally assessed. Barriers and facilitators of inclusive health research were presented. Four recommendations for inclusive health research were made. Abstract: Actively involving people with intellectual disabilities (ID) in health research, also known as inclusive health research, is increasingly popular. Currently, insight into experiences of this type of research is scarce. To gain insight into this topic, a structured literature review was conducted focussing on (1) existing theories, (2) inclusive methods, (3) added value and (4) barriers and facilitators. Literature published between January 2000 and January 2014 was included covering keywords related to ID and inclusive health research. Searches were performed in Pubmed, CINAHL, PsycINFO, EMBASE and MEDLINE databases, resulting in 26 included papers. Papers were quality assessed and analysed using qualitative data analysis software. Four theories were often simultaneously addressed: participatory research, emancipatory research, inclusive research and Arnstein's ladder. Barriers and facilitators could be divided into preparing, undertaking and finalising phases of research. Authors indicated that their motivation to conduct inclusive health research was based on demands by policy and funding bodies or was based on ethical considerations (i.e., ethical notions and giving people with ID a voice). Upon completion, authors perceived increased quality and validity of their research and several benefits for stakeholders (i.e., people with ID, researchers and healthcare professionals). Overall, there was consistency in their perception of the most important aspects of inclusive health research. Based on the analysis of included papers, four recommendations of inclusive health research with people with ID were found. Inclusive health research should be: (1) tailoring to the specific study; (2) anticipating all stakeholders; (3) considering its added value; and (4) providing insight into its process.